Determining Optimal Routes to Surgery for Borderline Resectable Venous Pancreatic Cancer—Where Is the Least Harm and Most Benefit? - Rupaly Pandé; Keith J. Roberts; Keith J. Roberts (Frontiers in Oncology, 2019)
Surgery among patients with borderline resectable pancreatic cancer (BRPC) and venous disease has emerged as a viable strategy to achieve curative treatment. By definition, these patients are at increased risk of a positive resection margin, however, controversy exists with regards to necessity of radical surgery and optimum pathways with no consensus on definitive treatment. A surgery first approach is possible though outcomes vary but patients can have an efficient pathway to surgery, particularly if biliary drainage is avoided which limits overall complications. Neoadjuvant therapy (NAT) is emerging as a widely used strategy to improve oncological outcomes, including resection margin status. However, some patients progress on NAT whilst others suffer major complications whilst elderly patients are unlikely to be offered effective NAT limiting the widespread applicability of this therapy. In this article an overview of the entire pathway is presented along with assimilation of current best evidence to determine optimal routes to surgery for BRPC with venous involvement.